Pengaruh Layanan Bimbingan Kelompok Melalui Metode Dzikir dalam Meningkatkan Ketenangan Jiwa pada Santri - Thomas Alfajar; Kusnadi Kusnadi (Journal of Society Counseling, 2025)
Inner peace plays a crucial role in the lives of students (santri) at Islamic boarding schools, since without it, the educational process and social interaction may be significantly disrupted. A lack of inner peace among santri can be triggered by dissatisfaction with oneself, negative thinking patterns, difficulty expressing emotions, and social pressure arising from adaptation to a new environment. This study aims to determine the effect of group counseling services using the dhikr method on increasing the inner peace of santri at Al-Ittifaqiah Islamic Boarding School, Indralaya. The study employed a quantitative approach with a one-group pretest-posttest experimental design involving 27 santri. The multiple linear regression analysis showed that the dhikr method (X) contributed 72% to santri's inner peace (Y), while the remaining 28% was influenced by other variables outside this study. The hypothesis test (independent sample t-test) yielded a significance value of 0.000 < 0.05, indicating that Ha was accepted and Ho was rejected. It is concluded that group counseling through the dhikr method is effective in enhancing santri's inner peace, reinforcing prior findings that Islamic spiritual approaches, including dhikr, play a significant role in community-based mental health interventions.